Quantification and modelling life satisfaction among internal displacees in Arda Transau, Zimbabwe - Mandishekwa, Robson; Mutenheri, Enard (Inderscience Publishers, 2021)
This study was prompted by the scarcity of literature on life satisfaction among mining-induced displacees in less developed economies. The study therefore quantified life satisfaction and determined the correlates of life satisfaction among internally displaced persons (IDPs) in Arda Transau. It was found that generally life satisfaction has not largely changed between pre-and post-displacement periods but the change was statistically significant. Ordered Logit Model results indicate that current life satisfaction is significantly determined by household size, social capital and neighbourhood characteristics while future life satisfaction depends on social support, perceived health status and neighbourhood characteristics. Recommendations from the study include that individuals must make use of their social connectedness to derive maximum benefits since social capital and social support were found to be among the major determinants of life satisfaction among IDPs.